Network topology of the desert rose - Hope, Sigmund M.; Kundu, Sumanta; Roy, Chandreyee; Manna, Subhrangshu S.; Hansen, Alex (Frontiers in Physics, 2015)
Desert roses are gypsum crystals that consist of intersecting disks. We determine their geometrical structure using computer assisted tomography. By mapping the geometrical structure onto a graph, the topology of the desert rose is analyzed and compared to a model based on diffusion limited aggregation. By comparing the topology, we find that the model gets a number of the features of the real desert rose right, whereas others do not fit so well.